Covering and explaining conflict in civil society - Nalini, Rajan ,Ed.; Rajan, Nalini (New Delhi: Orient Black Swan, 2014)
Contributed articles.
part I. Covering conflict in civil society -- part II. Explaining conflict in civil society -- part III. Civil society in social media.
Includes bibliographical references.
Keywords: Civil society; Conflict management; Social conflict in mass media; Social media